2019
DOI: 10.1002/adma.201806705
|View full text |Cite
|
Sign up to set email alerts
|

Solids Under Extreme Shear: Friction‐Mediated Subsurface Structural Transformations

Abstract: reducing energy consumption is a seemingly unlikely candidate: tribology. Tribology is the study of interacting surfaces in relative motion, including friction, wear and lubrication. In the transportation sector, a third of the energy consumed is lost by overcoming friction. [2] As far back as 1977, it was estimated that 11% of the energy used by the transportation, the industrial and the utilities sectors could be saved by new developments in tribology. [3] Although the term "tribology" was only coined in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 101 publications
1
36
0
Order By: Relevance
“…. It is widely reported that deformation due to sliding contact of metals is confined to a thin surface layer 28,29,[31][32][33][34][35][36][37] , typically about 100 nm, whereas the volume that participates in supporting the normal force is much larger 38 even at relatively mild contact stresses like those used here. The bulk hardness or flow stress can be converted into a shear strength using the approximation…”
mentioning
confidence: 85%
“…. It is widely reported that deformation due to sliding contact of metals is confined to a thin surface layer 28,29,[31][32][33][34][35][36][37] , typically about 100 nm, whereas the volume that participates in supporting the normal force is much larger 38 even at relatively mild contact stresses like those used here. The bulk hardness or flow stress can be converted into a shear strength using the approximation…”
mentioning
confidence: 85%
“…These microstructural modifications alter the properties of the material in the subsurface area and in turn affect friction and wear [7][8][9] . However, the underlying elementary deformation mechanisms are not sufficiently clear to allow for systematic modifications or even predictive simulation 10 . Atomistic simulations in nanocrystalline structures have demonstrated that the inhomogeneities of plastic deformation in the different grains and grain rotation play a significant role in tribologically induced deformation and wear 11 .…”
mentioning
confidence: 99%
“…According to the EBSD results, the lattice orientation of grains exhibiting hardening is substantially different from neighbouring orientations. Thus, the number of their potential gliding planes with low Schmidt factors [29] differs a lot. The number of available slip planes is regarded as the main reason for the inhomogeneity of strain accumulation along the contact surface.…”
Section: Discussionmentioning
confidence: 99%